Penguatan Identitas Kain Sasirangan Melalui Diversifikasi Motif Kontemporer dan Transformasi Pemasaran Digital - Siti Aliyati Albushairi; Ahmad Ahmad; Riza Firdaus; Nuril Huda; R.Roro Yulianti P; Abdurrahman Sadikin; Iqbal Maulana Huda; Chairul Saleh (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2026)
Sasirangan cloth is a cultural heritage of Banjarmasin City, possessing historical, philosophical, and economic value as a leading product of the craft sub-sector. However, the development of the modern fashion industry and digital transformation has caused MSMEs producing sasirangan cloth to face various challenges, particularly in motif innovation, business management, and digital marketing. Sasirangan products are still dominated by traditional motifs, making them less attractive to the younger generation, who tend to prefer contemporary designs and digital media-based promotions. Furthermore, limited digital literacy and the suboptimal use of social media and marketplaces have resulted in low product competitiveness in an increasingly competitive market. This Community Service Program (PkM) aims to strengthen the identity of sasirangan cloth through contemporary motif diversification and digital marketing transformation to increase the competitiveness of MSME artisans in Banjarmasin City. The implementation method is carried out through stages of socialization and training. Key activities include promoting the use of websites for MSME product marketing and training in Artificial Intelligence (AI)-based motif design. This program has resulted in innovative contemporary sasirangan motifs that maintain the philosophical values ​​of local culture, increased artisan capacity in business management and digital marketing, and developed a website for product promotion and branding. With this program, it is hoped that MSMEs producing sasirangan cloth will be able to increase product visibility, expand market reach, and strengthen the sustainability of the local wisdom-based creative economy in Banjarmasin City.